Analysis on Loneliness Levels of Students in Summer School of Physical Education and Sports School - Ozdayi, Nahit; Yücel, Ali Serdar; Demir, Mehmet Burak (Asian Journal of Education and Training, 2019)
The purpose of this study is to analyze the loneliness levels of students studying in 2017-2018 summer school of Balıkesir University School of Physical Education and Sports by some demographic characteristics. This is a descriptive study. The research population is composed of 865 students studying in 2017-2018 summer school of Balıkesir University School of Physical Education and Sports and the sample is composed of randomly selected 348 students. “UCLA Loneliness Scale” adapted into Turkish by Demir (1989) was applied in the study. The overall reliability of the loneliness scale was found to be α = 0.74. Kolmogorov Smirnov test was evaluated for the conformity of UCLA Loneliness Scale to the normal distribution in data analysis. Since all data were observed not to be normally distributed, Mann Whitney U and Kruskal Wallis tests ranked among the non-parametric tests were performed to compare the loneliness levels. All analyses were performed with SPSS v17.0 (SPSS Science, Chicago, IL, USA). In conclusion, it has been determined that the loneliness levels of the participants are high (51.07%), there is no statistically significant difference by the variables of sex, age, adequate leisure time, recreation and the place of residence while significant differences have been observed by the variables of department, branch and grade.